Development of Instructional Model to Promote and Create in Critical Thinking for Vocational Students based on Theory of Constructivism - Banchuen, Kijja; Chaturanon, Wimonrat (Ratchaphruek Journal, 2014)
The purpose of this research was to development of instruction model to promote and create in critical thinking for problem solving of vocational students based on constructivism theory. The samples were 68 students on second year in academic year 2013 at Samutprakarn Technical College selected by using purposive sampling technique. There were equally 34 students in the experimental and control groups. The research instruments consisted of 1) the development of instruction model to promote and create in critical thinking for problem solving of vocational students based on constructivism theory, 2) the developed instruction model lesson plans and normal lesson plans, 3) the critical thinking for problem solving test, and 4) the satisfied questionnaires. The analyzing statistic was percentages, mean standard deviation and hypothesis t-test (Independence Samples) The results of this research found that the instruction model to promote and create in critical thinking for problem solving of vocational students based on constructivism theory was developed. It consisted of 5 majors which were components, principles, objectives, contents, instruction process and evaluation. The instruction processes were 5 phases; 1) Identifying theproblem,2) Reflecting information, 3) analyzing, 4) Evaluating hypothesizes, and 5) Concluding knowledge for problem solving. The average scores of the critical thinking for problem solving test after using the developed model learning was higher than the control group at 0.5 level of significance the satisfactions of the experimental group are at a highest level.